Efektivitas Pembiayaan Produk Qardhul Hasan pada Bank Kalsel Syariah Cabang Banjarmasin - Masrina Masrina; Khabib Musthofa; Dewi Safitri (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
Qardhul Hasan in Islamic banking is one of the instruments in the tabarru contract of all kinds of agreements involving not-for-profit transactions (non-profit transactions). So in essence Qardhul Hasan is not intended to seek commercial advantage for banks or institutions that use this product. This type of research is field research, while the nature of this research is qualitative research. The subjects in this study were Bank Kalsel employees and the object of this research was Qardhul Hasan product financing at the Banjarmasin Branch of Bank Kalsel. The data collection technique used in this study was by direct interviews with the respondents. The results of this study indicate that the mechanism was carried out by collecting donations from Bank Kalsel employees and also from customers. The funds are managed by the ZIS Management Agency, after which the funds collected are capital for benevolent funds which are channeled through Qardhul Hasan Products. As for the practice, it can be said to be effective in relation to strategy and management, namely the fulfillment of sharia principles, the fulfillment of the precautionary principle, the fulfillment of a competitive Islamic banking system, the fulfillment of achieving systemic stability and the realization of benefits for society.